PERANCANGAN MAXIMUM POWER POINT TRACKING PADA WINDBELT GENERATOR DENGAN ALGORITMA PERTURB & OBSERVE - Aulia Rakhman; Sujono Sujono; Eka Purwa Laksana (FAKULTAS TEKNIK UNIVERSITAS BUDI LUHUR, 2022)
Renewable energy is energy that comes from natural elements and its availability will not run out because it is formed from sustainable natural processes. Renewable energy is an alternative energy to replace fossil energy because it is environmentally friendly and does not produce carbon emissions. Renewable energy sources come from sunlight, wind, water flow, geothermal, etc. One of the renewable energy potentials in Indonesia is wind energy with a total potential of 60.6 GW. Utilization of wind energy can be done by using wind turbines and windbelts to convert wind energy into electrical energy. Windbelt is a device consisting of a permanent magnet, coil and tape to produce electrical energy. When the oscillating band is blown by the wind, the magnet produces a change in magnetic flux, then the magnetic flux captured by the coil produces induced emf at both ends of the coil. In order for the power generated by the windbelt to remain at its maximum point even though the wind speed fluctuates, a Maximum Power Point Tracking (MPPT) system is needed. Therefore, in this study, an MPPT system was designed using the Perturb & Observe (P&O) algorithm by controlling the length and tension of the band based on the windbelt output voltage. The optimal voltage generated by the windbelt is 8.93 Volts without using the MPPT system, while when using the MPPT system the optimal voltage is 5.05 Volts. In testing the MPPT system using a load (condition 2), the output voltage has decreased drastically because the current generated by the windbelt is so small that it cannot pass through the load.